Work discussion seminars: a psychoanalytic approach to training community childcare workers - Sosnovik, Nicole (My University, 2014)
The aim of this study was to consider the contribution that psychoanalytically-informed work can make to the training of workers in the field of Early Childhood Development in South Africa. The model chosen for the purposes o f this study was the Work Discussion Seminar, based on a model developed at the Tavistock Clinic in London. Six subjects, all educate workers running their own creches, were recruited. Five out o f the six participants belonged to the Impilo Pilot Project, an action research project launched by the Gauteng Department o f Education in 1997. The subjects took part in six Work Discussion Seminars once a week, for six weeks. Discussions focused upon the behaviour and inner preoccupations o f various children, as well as on the conscious and unconscious responses o f the workers to these children’s communications. The seminars were based upon, the view that caregivers of young children need nurture and understanding themselves, in order to fulfil the demanding role of child rearing. Data from recordings o f discussions in the sessions and from preand post-interview measures showed that the participants appreciated the opportunity o f working in a group, which encouraged the sharing o f ideas and also provided containment for their work-related anxieties. In addition, it revealed that the impact of discussions extended beyond the boundaries o f the seminars themselves in that suggestions made and understandings reached were shared with creche assistants, as well as with the parents o f the children concerned.